The Influence of the Quantum Teaching Model in Improving Students' Critical Thinking Skills in Elementary School Science Learning: Pengaruh Model Quantum Teaching dalam meningkatkan keterampilan berpikir kritis siswa pada pembelajaran ipas sekolah dasar - Amalia Restuana Dewi; Widiyono, Aan (Journal of Practice Learning and Educational Development, 2026)
This study aims to annalyze the influence of the Quantum Teaching model on enhancing students’ critical thinking skills in Natural and Social Science (IPAS) learning for fifth-grade students at SDN 01Petekeyan. The  research employed a One Group Pretest-Posttest design of the Pre-Experiment type. A total of  32 fifth-grade students partisipated, consisting of 22 males and 10 females. The research instruments were pretest and posttest questiond that had been validted and tasted for reliability. Data analysis involved normality tests, homogeneity tests, and paired sample t-tests conducted using SPSS application. The Results showed a significant improvement in students’ critical thinking skills following the implementation of the Quantum Teaching model, with the average pretest score increasing from 58.38 to 77,75 i n the posttest. The t-test analysis yielded a significance value of 0,000 <0,05 indicating that the Quantum Teaching Model had a significant effect on improving students’ critical thinking skills. This model proved to be effective in cretting an interactive, enjoyable, and meaningful learning environment while encouraging students to think reflectively and actively solve problems.